Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 4759 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 2000", "Month is greater than or equal to January", "Country is China", "TaxonKey is Fungi" ] } The dataset includes 4759 records from 30 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003104-170714134226665/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences